Spatio-Temporal Pattern of Interprovincial Migration of Rural Population in China and Its Influencing Factors - Wenyue Zhong; Yuanzhi Guo (Applied Sciences)
In the era of significant migration, the rural population has been a major component of China’s internal migration. Utilizing data from the last three population censuses, this study examines the evolution and network characteristics of interprovincial rural migration in China from 2000 to 2020. A panel model is employed to analyze the influencing factors. The findings reveal that the interprovincial migration of China’s rural population has increased rapidly, though the growth rate has decelerated. Provincial rural emigration scales have shown a differentiated trend, with the Heihe-Tengchong Line serving as a boundary, while the overall pattern exhibits a “center-periphery” structure. The primary migration destinations are the eastern coastal provinces. Between 2000 and 2020, China’s interprovincial rural migration network demonstrated strong centralization, but the agglomeration core of the network became more diversified. Spatially, interprovincial rural migration shows a clear preference for proximate destinations, and the interprovincial migration network has gradually shifted from an “umbrella-shaped” pattern to a “funnel-shaped” pattern. Key factors influencing the evolution of the interprovincial rural migration network include the per capita GDP, natural disasters, topographic relief, spatial distance, rural hukou population, and internet penetration rate. To facilitate orderly rural migration and support the major national strategies, it is essential to promote regional coordinated development, deepen rural hukou system reforms, and streamline factor flow mechanisms.